P007 ORMDL proteins shape homeostasis in the intestinal epithelium by regulating endoplasmic reticulum architecture and autophagy. (21st January 2022) - Tran, F; Stengel, S; Yang, H; Bernardes, J P; Lopez-Agudelo, V; Bordoni, D; Falk-Paulsen, M; Jentzsch, M; Messner, B; Schreiber, S; Rosenstiel, P
Abstract: Background: ORM1-like protein 3 (ORMDL3) is an endoplasmic reticulum (ER)-resident protein that has been implicated in ER homeostasis and sphingolipid biosynthesis. Genome-wide association studies identified susceptibility loci around the ORMDL3 gene for inflammatory diseases, including asthma and IBD. Preliminary studies suggested a role of ORMDL proteins within the ER stress-induced unfolded protein response (UPR). Here, we set out to investigate the role of ORMDL proteins in intestinal inflammation. Methods: Mice with constitutive and conditional knockouts (KO) of Ormdl1, Ormdl2 and Ormdl3 in intestinal epithelial cells were generated. From these, intestinal organoids were generated to perform functional assessment of ER stress, autophagy, and inflammatory responses. We performed 3'-single cell RNA sequencing (scRNAseq) of small intestine tissue of animals with triple conditional knockout of Ormdl1 / Ormdl2 / Ormdl3 (" Ormdl123 -VilCre") vs. wildtype to identify cell type-specific effects of epithelial ablation of ORMDL proteins. 16S rDNA sequencing was performed on stool samples from these animals. Results: Mice deficient for ORMDL displayed reduced body weight dependent on the number of knockouts. Ormdl1 / 2 / 3 -KO mice are embryonically lethal while Ormdl1/2/3 -VilCre animals were viable without signs of spontaneous inflammation. Ormdl1 - and Ormdl3 -KO animals displayed reduced number of Paneth and goblet cells in the small intestine, accompanied by massive dilation/ballooning of the ER. This phenotype was strongly pronounced in Ormdl1/3 -KO and Ormdl1/2/3 -VilCre animals. ORMDL3 co-localises and co-precipitates with LC3, indicating a direct interaction with autophagy proteins, while loss of ORMDL proteins impaired autophagic flux. Interestingly, UPR and Cxcl1 expression were insufficiently induced in intestinal organoids from Ormdl1/2/3 -VilCre animals treated with tunicamycin. scRNAseq analysis of small intestine tissue surprisingly revealed compensatory induction of antimicrobial peptides in non-Paneth cells and vice versa downregulation of apoptosis regulating gene in Ormdl1/2/3 -VilCre mice. We observed an expansion of myeloid and plasma cells in Ormdl1/2/3 -VilCre mice, while no changes in epithelial cell proportions can be identified. These findings were accompanied by dysbiosis of the stool microbiome (β-diversity, Bray-Curtis dissimilarity) of Ormdl1/2/3 -VilCre animals. Conclusion: Our data suggest a critical regulatory role of the IBD risk gene ORMDL3 in the ER-autophagy axis in intestinal epithelial cells, shaping the mucosa homeostasis on cellular and microbiome level. Functional assessment of inflammation in Ormdl1/2/3 -VilCre animals (e.g., DSS colitis model) will be performed to understand the role of ORMDL in intestinal inflammation.